CRM1, a novel independent prognostic factor overexpressed in invasive breast carcinoma of poor prognosis - Yue, Lu (Oncol Lett, 2018)
Breast cancer (BC) is the most commonly diagnosed cancer in females globally and is more aggressive at later stages. Chromosome region maintenance 1 (CRM1) is involved in the nuclear export of proteins and RNAs and has been associated with a number of malignancies. However, the clinicopathological significance of its expression in BC remains to be elucidated therefore this was investigated in the present study. CRM1 expression in 280 breast cancer tissues and 60 normal tissues was retrospectively analyzed using immunohistochemistry (IHC) and western blotting. IHC investigation demonstrated that CRM1 expression was significantly increased in BC compared with the normal breast epithelium (P<0.0001). Overexpression of CRM1 was markedly associated with poor prognostic characteristics, including larger tumor size (P=0.024), positive lymph node metastasis (P=0.032), invasive histological type (P=0.004) and distant metastasis (P=0.026). Significant associations were also observed between increased CRM1 expression and the progesterone receptor (P=0.028) and Ki67 (P=0.019). Kaplan-Meier survival analysis demonstrated that patients with high CRM1 expression exhibited a reduced disease-free survival and overall survival compared with those with low CRM1 expression (P=0.013). In the multivariate analysis, CRM1 expression (P=0.011), tumor size (P=0.001) and lymph node metastasis (P<0.001) were independent prognostic markers of BC. In conclusion, CRM1 serves an important role in BC and may serve as a predictive and prognostic factor for a poor outcome in patients with BC.